Analisi della città Brasiliana e metodologie di riqualificazione urbana - DOI: 10.5752/P.2316-1752.2009v16n18/19p287 - Lengueglia, Luca (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This paper, resulting from the work carried out by students during the Summer Course held in Belo Horizonte, aims to identify, in a clear and concise way, regions of the Brazilian city, where two large categories can be perceived: the formal and the informal city. Subsequently, it examines the best urban development methodologies and what they comprise. Key words : Formal city; Informal city; Urban development.